(untitled) (Bheshaja: Journal of Central Ayurveda Campus, 2025)
Introduction: Anal fistulas can be considered complex when there are ramifications, internal opening is present proximal to pectinate line, has multiple openings, is supra-sphincteric or extra-sphincteric course. Managing complex anal fistulas is a matter of challenge due to high recurrences and surgical complications. Managing fistula-in-ano through Ksharasutra (Ayurvedic medicines coated surgical thread) has been practiced for decades which when integrated with modern interception techniques has been associated with very less recurrences and no or very minimal surgery related complications even in complex anal fistulas. Methodology: A 59 years old male with 2 years history of complex fistula-in-ano has been operated under saddle block where complex fistulous track was intercepted at the level of external sphincter followed by application of Ksharasutra. Patient has been kept under proper post-operative care and the Ksharasutra has been changed weekly till the track is cut open. Result: Complete healing of the fistulous tracks occurred after 3 months without any significant post-operative adverse events. Patient didn’t have any recurrence till the date and is living a good quality life now. He has got relief from all his previous signs and symptoms. Discussion: Ksharasutra drains out the infective tissues of track and cures the cryptoglandular infections. Long tracks when intercepted separates track into two so that the track distal to the interception when drained properly collapses on its own so, there is no need to create big wounds to take out all fistula tracks. Sphincter damage by Ksharasutra is very minimal which barely can cause anal incontinence. Interception of complex fistula-in-ano with application of Ksharasutra has been found to be effective as well as very safe procedure.